1991
DOI: 10.1111/j.1600-0404.1991.tb04664.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of nocturnal sleep in patients with HIV infection

Abstract: Nocturnal sleep of 14 patients with HIV infection was characterized by longer sleep onset latency, shorter total sleep time, reduced sleep efficiency, more time spent awake and in Stage 1. There was significantly less sleep Stage 2 than in healthy controls. REM latency was slightly reduced and correlated negatively with depressive symptomatology, while percentages of REM and slow wave sleep were normal. Patients without complaints at the time of the investigation exhibited similar sleep abnormalities. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 4 publications
2
15
0
2
Order By: Relevance
“…This means that depression, which occurs frequently and severely during all stages of HIV infection [28], is the main factor associated with sleep disturbances in HIV infected patients and is independent from immunological parameters. This confirms previous findings on insomnia, fatigue, and polysomnographic changes in HIV infection which are also determined nearly exclusively by psychological comorbidity and not by the immune state of the patients [3,6,10,29]. However, the causal relationship between depression and sleep disorders remains unclear in our sample.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This means that depression, which occurs frequently and severely during all stages of HIV infection [28], is the main factor associated with sleep disturbances in HIV infected patients and is independent from immunological parameters. This confirms previous findings on insomnia, fatigue, and polysomnographic changes in HIV infection which are also determined nearly exclusively by psychological comorbidity and not by the immune state of the patients [3,6,10,29]. However, the causal relationship between depression and sleep disorders remains unclear in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…REM latency was slightly reduced and correlated negatively with depressive symptomatology, while percentages of REM and slow wave sleep were normal [10]. These findings were independent from the immune state of the patients in most studies [4,9,10].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a survey study of 115 HIV clinic patients, 73% endorsed insomnia [60]. Poor sleep quality in HIV-infected patients accompanies higher levels of depressive, anxiety, and physical symptoms; daytime sleepiness; and cognitive and functional impairment [61].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…It has been shown that disturbances in sleep can affect the normal physical, mental, and emotional functioning in human immunodeficiency virus (HIV)-infected individuals [1,2]. These individuals have been known to have a high prevalence of disturbance ranging from 40% to 70% [3][4][5].…”
Section: Introductionmentioning
confidence: 99%